2011
DOI: 10.1590/s1808-86942011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular range of motion in patients with idiopathic peripheral facial palsy

Abstract: regardi ng orofacial motor assessment in facial paralysis, quantitative measurements of the face are being used to establish diagnosis, prognosis and treatment planning. Aim:To assess the prevalence of changes in mandibular range of motion in individuals with peripheral facial paralysis.Materials and Methods: prospective study. We had 56 volunteers, divided in two groups: G1 made up of 28 individuals with idiopathic facial paralysis (6 males and 22 females); 14 with manifestations on the right side of the face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
6
0
8
Order By: Relevance
“…The results of the study suggest that for each group with longer duration of the paralysis, the sequelae of the facial lesion are more evident. According to the literature, the change in facial muscle functions is a condition, which may be associated to vegetative alterations such as the absence or reduction of tearing, vascular alterations, or co-contractions of surrounding muscles in the case of functional muscle imbalance, as in the case of facial palsy (25) . A recent prospective study, which evaluated 259 patients with peripheral facial palsy (19) , concluded that despite the importance of clinical evaluation protocols in the follow-up of facial palsy patients' recovery, the evaluation by invasive EMG is able to provide more accurate data on the degree of facial motor impairment of the patient and, therefore, it allows predicting the possibility of facial movement recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study suggest that for each group with longer duration of the paralysis, the sequelae of the facial lesion are more evident. According to the literature, the change in facial muscle functions is a condition, which may be associated to vegetative alterations such as the absence or reduction of tearing, vascular alterations, or co-contractions of surrounding muscles in the case of functional muscle imbalance, as in the case of facial palsy (25) . A recent prospective study, which evaluated 259 patients with peripheral facial palsy (19) , concluded that despite the importance of clinical evaluation protocols in the follow-up of facial palsy patients' recovery, the evaluation by invasive EMG is able to provide more accurate data on the degree of facial motor impairment of the patient and, therefore, it allows predicting the possibility of facial movement recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the temporomandibular joint with CMT has been shown to help improve mandibular range [12]. The mandibular range of motion in patients with facial palsy is an essential factor because mandible movements enable changes in the intraoral spaces, allowing for free movements of the tongue and the soft tissue [23]. In addition, some articles denote that patients with facial palsy have a significant reduction in the mandibular range of motion when compared to the control group [12].…”
Section: Resultsmentioning
confidence: 99%
“…Other articles were found 10,18,19,22,26,34 in which the HB scale was used by a neurologist or SLH therapist.…”
Section: Description Of the Instruments Found In The Researchmentioning
confidence: 99%